Conventional Treatment for Multiple Myeloma Drives Premature Aging Phenotypes and Metabolic Dysfunction in T Cells - Cooke, Rachel Elizabeth; Quinn, Kylie Margaret; Quach, Hang; Harrison, Simon; Prince, Henry Miles; Koldej, Rachel; Ritchie, David (Frontiers in Immunology, 2020)
New diagnoses of multiple myeloma (MM) tend to occur after the age of 60, by which time thymic output is severely reduced. As a consequence, lymphocyte recovery after lymphopenia-inducing anti-MM therapies relies on homeostatic proliferation of peripheral T cells rather than replenishment by new thymic emigrants. To assess lymphocyte recovery and phenotype in patients with newly diagnosed MM (NDMM) and relapsed/refractory MM (RRMM), we tracked CD4+ and CD8+ T cell populations at serial time points throughout treatment and compared them to age-matched healthy donors (HD). Anti-MM therapies and autologous stem cell transplant (ASCT) caused a permanent reduction in the CD4:8 ratio, a decrease in naïve CD4+ T cells, and an increase in effector memory T cells and PD1-expressing CD4+ T cells. Transcriptional profiling highlighted that genes associated with fatty acid β-oxidation were upregulated in T cells in RRMM, suggesting increased reliance on mitochondrial respiration. High mitochondrial mass was seen in all T cell subsets in RRMM but with relatively suppressed reactive oxygen species and mitochondrial membrane potential, indicating mitochondrial dysfunction. These findings highlight that anti-MM and ASCT therapies perturb the composition of the T cell compartment and drive substantial metabolic remodeling, which may affect the fitness of T cells for immunotherapies. This is particularly pertinent to chimeric antigen receptor (CAR)-T therapy, which might be more efficacious if T cells were stored prior to ASCT rather than at relapse.